2010
DOI: 10.1128/aem.00203-10
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Decarboxylase-Mediated Nisin Resistance in Listeria monocytogenes

Abstract: Analysis of a complete set of glutamate decarboxylase (gad) mutants of Listeria monocytogenes strain LO28 (⌬gadD1, ⌬gadDT1, ⌬gadD2, ⌬gadT2, and ⌬gadD3 mutants) revealed that the ⌬gadD1 mutant is impaired in its ability to tolerate exposure to both sublethal and lethal levels of the lantibiotic nisin. gadD1 is strain variable and is found only in approximately 50% of L. monocytogenes strains. Growth and survival experiments revealed that possession of gadD1 correlates with a higher degree of tolerance to nisin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 25 publications
1
48
0
Order By: Relevance
“…No role for GadD3 in acid tolerance has been established, although a gadD3 insertion mutant has been shown to be defective for intracellular growth (11). Recently, the construction of a gadD3 deletion mutant has been reported by Begley et al (2). However, in this work it was demonstrated that unlike GadD1, GadD3 does not play a role in nisin resistance, but no role in acid resistance was investigated.…”
mentioning
confidence: 84%
“…No role for GadD3 in acid tolerance has been established, although a gadD3 insertion mutant has been shown to be defective for intracellular growth (11). Recently, the construction of a gadD3 deletion mutant has been reported by Begley et al (2). However, in this work it was demonstrated that unlike GadD1, GadD3 does not play a role in nisin resistance, but no role in acid resistance was investigated.…”
mentioning
confidence: 84%
“…gadT1 and gadT2 encode antiporters which import glutamate and export GABA. Deletion of gadD1 impairs the ability of a strain to tolerate exposure to both sublethal and lethal levels of nisin (200). It was discovered that the intracellular ATP levels were reduced in the ⌬gadD1 mutant, being only approximately 60% of those of the parent, suggesting that GadD1 contributes significantly to ATP pools and hence to tolerance of nisin (200).…”
Section: Gad Systemmentioning
confidence: 99%
“…Assessing the extent of induced nisin resistance among multiple strains is important in light of previous studies demonstrating variation in innate nisin resistance linked to a genomic island that is variably present in ϳ50% of L. monocytogenes genomes (10). Our data indicate that while salt-induced nisin resistance does occur in all the strains tested, variation in the extent of the protective effect of salt does exist.…”
Section: Discussionmentioning
confidence: 56%